Monitoring Air Quality Around Users With IOT Based NODEMCU ESP8266 - Zaky Wahyu Oktavianto; Anton Breva Yunanda (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
For regional issues and issues related to a healthy environment, there were issues related to water and air quality. The biggest source of air pollution is vehicle exhaust fumes, and the increase in the number of vehicles in Sidoarjo City grows by an average of 18 percent per year. To overcome this problem, an air quality monitoring device is needed. The goal to be achieved by creating an air quality monitoring system as an Internet of Things application is to become a prototype for monitoring environmental health problems related to air quality in Sidoarjo City. Monitoring is carried out online through the Thingspeak IoT platform. This tool applies Ohm's law theory to reading conversion calculations when the MQ sensor operates as a CO, CO2, and Acetone gas detector. NODEMCU ESP8266 as microcontroller. This tool can be used as a prototype for monitoring in highway areas with high vehicle intensity.